Assessment of Requirements for the Creation of Course Materials for English as a Second Language for Students Majoring in Subjects Other Than English - Alouzi, Khuloud Mustafa (Majapahit Journal of English Studies, 2024)
The most important thing for the success of a language learning program, including English as a general course, is making sure that the right tools are used. Before the materials are made, the needs of the students should be figured out so that the person making the materials has a full picture of what the students need. The study's goal is to find out what the students want to create tools for English as a general course for students who are not in the English Department. Twenty-four students from various areas at Universitas Tidar took part in the study. The study used a method called quantitative research, and a questionnaire was used to collect the data. The results show that the students want to learn English for their future jobs and to communicate with people around the world. The kids also say they need to improve their grammar and pronunciation, as well as their speaking, reading, and writing skills. The students also say that grammar is the hardest part of language to learn and that listening is the hardest macro skill to master. In terms of the issues, the students say that the materials should cover English for everyday, professional, and academic purposes. Concerning the creation of in-class activities, the things that students are most excited about are practicing pronunciation, learning new words, and watching English-language videos. On the other hand, they would rather make videos and work on a project as homework. They also get more excited when working in groups than when working alone or in pairs.